2005
DOI: 10.1124/jpet.105.089342
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium (II)-Derived Organometallic Compounds Induce Cytostatic and Cytotoxic Effects on Mammalian Cancer Cell Lines through p53-Dependent and p53-Independent Mechanisms

Abstract: The metallic compound cisplatin has been used for many years to treat various human cancers. Here, we describe the cytostatic and cytotoxic properties of a new class of organometallic compounds that contain a ruthenium (II) atom covalently linked to carbon and nitrogen atoms. We found that several ruthenium-derived compounds (RDCs) led to G 1 arrest and induced apoptosis in tumor cell lines derived from glioblastomas, neuroblastomas, and lymphoid tumors at least as efficiently as cisplatin. We further analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 38 publications
1
100
0
Order By: Relevance
“…Indeed, several ruthenium-containing drugs interact with DNA and modify its structure, suggesting that they might induce DNA damages. Activation of p53 or p73 by some of these drugs partly corroborated this hypothesis (23)(24)(25). Alternative modes of action have also been described, including production of reactive oxygen species (26), inhibition of kinases (27), modification of enzymatic activities (28), or redox reactions (29).…”
Section: Introductionmentioning
confidence: 57%
“…Indeed, several ruthenium-containing drugs interact with DNA and modify its structure, suggesting that they might induce DNA damages. Activation of p53 or p73 by some of these drugs partly corroborated this hypothesis (23)(24)(25). Alternative modes of action have also been described, including production of reactive oxygen species (26), inhibition of kinases (27), modification of enzymatic activities (28), or redox reactions (29).…”
Section: Introductionmentioning
confidence: 57%
“…However, the mechanisms of action of ruthenium-based anticancer compounds are comparatively unexplored, although it is clear that ruthenium compounds interact far more weakly with DNA relative to platinum compounds [15]. There is evidence to suggest that ruthenium compounds might directly interfere with specific proteins involved in signal transduction pathways and/or alter cell adhesion and migration processes [10,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…11-16) Pfeffer and colleagues 17,18) and Chao and colleagues 19,20) have found that some cyclometalated ruthenium(II) complexes are good candidates for becoming anticancer drugs. A cyclometalated ruthenium fragment with a metal-carbon σ bond is a crucial element for a potential anticancer drug.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Several ruthenium complexes that display an activity comparable to that of cisplatin have been described, and in some cases activities are even better. [11][12][13][14][15][16] Pfeffer and colleagues 17,18) and Chao and colleagues 19,20) have found that some cyclometalated ruthenium(II) complexes are good candidates for becoming anticancer drugs. A cyclometalated ruthenium fragment with a metal-carbon σ bond is a crucial element for a potential anticancer drug.…”
mentioning
confidence: 99%